Efeito da citotoxicidade mediada por células Natural Killer em células-tronco de câncer derivadas de carcinoma epidermóide oral e sua associação com a terapia fotodinâmica - Ibarra, Ana Melissa Ccopa (2022)
INTRODUCTION: Oral squamous cell carcinoma (OSCC) is an aggressive neoplasm with high rates of recurrence, the progression of this neoplasm leads to immunosuppression of the patient. Photodynamic therapy (PDT) is a promising therapy for promoting stimulation of the immune system mediated by stress signals after its interaction with the target, however, its effectiveness is limited in the absence of T and NK cells (Natural Killer). Thus, the objective of this work was to evaluate in vitro the role of NK cells in the elimination of cancer stem cells (CTC) in CEO as well as their activity after PDT. METHODS: The NK92-MI, Ca1 and Luc4 cells were characterized by flow cytometry and RT-qPCR, the cytotoxicity of NK92-MI in CEO was evaluated by CalceinAM release, the stem capacity of tumor cells were evaluated by sphere and colony; Ca1 and Luc4 were subjected to PDT, the dosimetry was established by assessing viability by MTS. After PDT the cytotoxic capacity of NK92-MI in CEO was evaluated again. RESULTS: The NK92-MI cells presented a CD45+/CD3-/CD56+ phenotype. Cells from the Ca1 and Luc4 lineages showed three different subpopulations defined by the CD44/ESA cytometry phenotype, with the amoeboid population defined by CD44high/ESAlow. The gene expression of NKG2D ligands varied among the subpopulations, the amoeboid subpopulation shows a reduction in ULBPs, HLA and an increase in MICA/B. CONCLUSION: The cytotoxic capacity of NK varied among subpopulations, amoeboid cells are more sensitive to NK attack. The stem capacity of the subpopulations was affected by the cytotoxic activity of NK, through the reduction of spheres and colonies formed as well as alterations in the subpopulation phenotypes, reducing the CD44high/ESAlow population meanwhile CD44low population increased. PDT induced cell death increasingly with increased radiant energy delivered and did not affect the cytotoxic activity of NK at the subdoses of 1.5J/cm² and 3J/cm² evaluated here.